A STUDY OF HAITIAN IMMIGRANT’S ASSIMILATION TO WESTERN PRACTICES OF USING THE TELEPHONY AND INTERNET TECHNOLOGIES - Đokić, Borivoje-Boris; Polak, Rhonda; Francis, Jeanette D.; Mujtaba, Bahaudin G. (The European Journal of Applied Economics, 2013)
This study examines the relationship between the use of technology to stay connected with home country and culture while adapting and integrating into the host culture. Through a survey the authors probe into how Haitian immigrants living in South Florida with varying levels of contact with their home country acculturate into the receiving society, exploring an increasingly salient experience of contemporary global migrants. Immigration is the experience of acculturation by individuals and the emergence of culturally plural societies, where both immigrants and host country citizens can live together in a positive environment. In this study, we report our exploratory findings and insights from a survey conducted among Haitian immigrants in South Florida area, studying the relationship between the scope of their electronic communication, and their level of integration into the mainstream American culture. Considerable research has been devoted to the understanding of immigration, acculturation and adaptation of adults, but much less has addressed these phenomena among Haitian population in reference to the use of communication technologies to keep in touch with their loved ones overseas and being fully adapted to their host country at the same time, asserting both identities. In other words, to what extend Haitians who wish to have contact with American culture, while maintaining their cultural attributes do so through the Internet and telecommunication technologies. The objective of this study is to explore the correlation between cultural integration process and the level of Internet and telephony technologies usage among Haitians living in South Florida. The Internet and telephones are a necessity becoming central for one’s knowledge of environment, for the retention of one’s social contacts but also for the organization of one’s life. This is especially true for immigrants who often rely on their new and old social networks in order to adjust to the host country. This study looks at five well understood measures or indicators of the acculturation process, namely language proficiency, language use, length of time in the host culture, age, and peer contact. It also looks at the preferences of Internet related tools to contact friends and relatives both in Haiti and the USA by email, text messaging, and social sites. In our study, highly integrated Haitian immigrants are those who are young, have lived here for a long time, are proficient in Creole and English, speak to friends and relatives in both languages, and spend their free time with both Americans and other Haitians.